Social and individual preconditions for intercultural communication - Marković Savić, Olivera S.; Bakić Mirić, Nataša M. (Sociološki pregled, 2022)
While multiculturalism is a political precondition for the legal guarantee and protection of minority groups, interculturality implies the establishment of relations between individuals or groups belonging to different cultures with the belief that human experience is enriched and developed through cultural contacts. In order for a person to understand other cultures, s/he must first of all know their own culture, which means language, religion, values, beliefs, norms and worldviews. Thus, current debates are particularly aimed at seeking an adequate relationship between modern nation-states and ethnic and national minorities that are either domiciled or new to their territories are of particular importance. Moreover, the solution is sought in intercultural communication as the next step that would embrace multicultural assumptions and lead individuals to respect their own and other cultures through the intercultural exchange that would be the final, desirable product of intended policies. The paper presents some of the assumptions for intercultural communication that help improve an interactive relationship with people and/or other cultural groups. The need to discuss these concepts lies in circumstances in which they cannot be ignored in the modern world, primarily because it is not possible to return to a time when groups with different cultural and identity backgrounds will no longer be interested in representing their diversity.